A multicenter phase II study of preoperative chemoradiotherapy with S-1 plus oxaliplatin for locally advanced rectal cancer (SHOGUN trial). Issue 2 (August 2015) - Matsusaka, Satoshi; Ishihara, Soichiro; Kondo, Keisaku; Horie, Hisanaga; Uehara, Keisuke; Oguchi, Masahiko; Murofushi, Keiko; Ueno, Masashi; Mizunuma, Nobuyuki; Shimbo, Taiju; Kato, Daiki; Okuda, Junji; et al.
Abstract Purpose This study was designed to evaluate the safety and efficacy of adding oxaliplatin to preoperative chemoradiotherapy (CRT) with S-1 in patients with locally advanced rectal carcinoma (LARC). Patients and methods This was a multicenter phase II study in patients with histologically proven clinical stage T3 or T4 (any N, M0) LARC. Patients preoperatively received oral S-1 (80 mg/m2/day on days 1–5, 8–12, 22–27, and 29–33) and infusional oxaliplatin (60 mg/m2 days on 1, 8, 22, and 29) plus radiotherapy (50.4 Gy), with a chemotherapy gap in the third week of radiotherapy. Pathological complete response (pCR) was the primary endpoint. Secondary endpoints included toxicity, compliance, R0 resection rate, and downstaging rate. Results A total of 45 patients were enrolled at six centers in Japan. All 45 patients received CRT, and 44 underwent operation. A pCR was achieved in 12 (27.3%) of the 44 patients who underwent surgery. Near-total tumor regression was confirmed in 47.7%. There were no grade 4 adverse events, and 11.1% of the patients had grade 3 adverse events. R0 resection was achieved in 95.5% of the patients. Conclusion Preoperative CRT with S-1 plus oxaliplatin had a high pCR rate and a favorable toxicity profile.